2020
DOI: 10.1186/s12301-020-00036-7
|View full text |Cite
|
Sign up to set email alerts
|

Bone mineral density in Nigerian men on androgen deprivation therapy for advanced prostate cancer

Abstract: Background Cancer of the prostate (CaP) is the most frequently diagnosed non-cutaneous malignancy worldwide, and it is the second leading cause of death from cancer in men. In the developing world, majority of patients with CaP present in advanced stage and often times, androgen deprivation therapy (ADT) is the only treatment option available. ADT has been reported to increase the risk of osteopenia and osteoporosis in patients with CaP in studies done predominantly among the Caucasians. There … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 33 publications
0
1
0
Order By: Relevance
“…These study results are in compliance with previous related cross-sectional studies. 4 , 12 Additionally, it was also noted that former ADT user’s experienced significant increase in BMD levels which predicted the probability of reversibility in ADT-associated bone loss. The study also revealed incidence of bone disorders (osteoporosis) was lower in cancer suffering men who didn’t undergo ADT but the difference was not significant than other study groups.…”
Section: Discussionmentioning
confidence: 99%
“…These study results are in compliance with previous related cross-sectional studies. 4 , 12 Additionally, it was also noted that former ADT user’s experienced significant increase in BMD levels which predicted the probability of reversibility in ADT-associated bone loss. The study also revealed incidence of bone disorders (osteoporosis) was lower in cancer suffering men who didn’t undergo ADT but the difference was not significant than other study groups.…”
Section: Discussionmentioning
confidence: 99%